Method for producing active material
By using a Li extraction solvent mixture of ethanol and other alcohols to extract Li from a LiSi precursor, the method effectively adjusts the pore size of active materials, addressing issues of pore collapse and expansion/contraction stability in battery applications.
Patent Information
- Application Number
- JP2022086156
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-05-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-05-26
AI Technical Summary
Existing methods for producing active materials with voids do not adequately allow for adjustment of pore size, which can lead to issues such as pore collapse during battery production and uneven expansion/contraction during charging and discharging.
A method involving the preparation of a LiSi precursor and the use of a Li extraction solvent containing ethanol and one or more of methanol and propanol to extract the Li element, forming voids and adjusting the pore size of the active material.
This method enables the production of active materials with adjusted pore sizes, reducing the likelihood of pore collapse and enhancing the stability of the active material during battery operation, thereby improving the battery's input/output characteristics and cycle performance.
Smart Images

Figure 0007661930000002 
Figure 0007661930000003 
Figure 0007661930000004
Abstract
Description
[Technical field]
[0001] This application discloses a method for making an active material. [Background technology]
[0002] Patent Documents 1 and 2 disclose a method for producing an active material having voids by extracting Li element from a LiSi precursor using a Li extraction solvent. Patent Documents 1 and 2 disclose ethanol, 1-propanol, 1-butanol, 1-hexanol, and acetic acid as Li extraction solvents. According to the techniques disclosed in Patent Documents 1 and 2, an active material with a small volume change during charging and discharging can be obtained. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-022554 [Patent Document 2] JP 2021-166153 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the prior art, there is room for adjusting the pore size of the active material. [Means for solving the problem]
[0005] As one of the means for solving the above problems, the present application provides: A method for producing an active material, comprising the steps of: Providing a LiSi precursor containing Li and Si elements; Extracting the Li element from the LiSi precursor using a Li extraction solvent to form voids; The Li extraction solvent comprises two or more selected from the group consisting of ethanol, methanol, and propanol; Disclose.
[0006] In the manufacturing method of the present disclosure, the Li extraction solvent may contain ethanol and one or more of methanol and propanol.
[0007] In the manufacturing method of the present disclosure, the Li extraction solvent may contain ethanol and propanol.
[0008] In the manufacturing method of the present disclosure, the Li extraction solvent may contain ethanol, methanol, and 1-propanol.
[0009] The manufacturing method of the present disclosure includes: mixing Si particles and Li metal to obtain the LiSi precursor; Dispersing the LiSi precursor in a dispersion medium to obtain a dispersion; and mixing the dispersion liquid with the Li extraction solvent to extract the Li element from the LiSi precursor and form voids. Effect of the Invention
[0010] According to the manufacturing method of the present disclosure, an active material with an adjusted pore size can be manufactured. [Brief description of the drawings]
[0011] [Figure 1] 1 shows an example of a flow of a method for producing an active material. [Diagram 2] The graph shows the relationship between the amount of pores with diameters of 55 nm or less in the active material and the increase in the confining pressure of the battery. [Diagram 3] For each of the active materials of Reference Examples 1 and 2, Example 3, and Comparative Examples 1 and 2, the relationship between the pore size and the pore volume is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] 1. Manufacturing method of active material An example of the flow of the active material manufacturing method is shown in Figure 1. As shown in Figure 1, the active material manufacturing method of the present disclosure includes preparing a LiSi precursor containing Li element and Si element, and extracting the Li element from the LiSi precursor using a Li extraction solvent to form voids. Here, the Li extraction solvent includes two or more selected from the group consisting of ethanol, methanol, and propanol.
[0013] 1.1 Preparation of LiSi precursor The LiSi precursor contains Li and Si elements. The LiSi precursor may be, for example, an alloy of Li and Si. The LiSi precursor may be any precursor capable of forming voids by extracting Li with a Li extraction solvent described later. The LiSi precursor may have a crystalline phase of Si (diamond type). The crystalline phase of Si has typical peaks at 2θ=28.4°, 47.3°, 56.1°, 69.2°, and 76.4° in XRD measurement using CuKα radiation. These peak positions may vary within a range of ±0.5°, or within a range of ±0.3°. The LiSi precursor may have a crystalline phase of Si (diamond type) as a main phase. The "main phase" refers to the crystalline phase to which the peak with the highest intensity belongs in the XRD chart. The LiSi precursor may have a crystalline phase of Si (diamond type). 22 The crystal phase of Si5 and Li 15 It may have a Si4 crystal phase. 22 The Si5 crystal phase has typical peaks at 2θ = 24.8° and 40.8° in XRD measurement using CuKα radiation, and Li 15 The Si4 crystalline phase has typical peaks at 2θ=20.3°, 26.2°, 39.4°, 41.2°, and 42.9° in XRD measurement using CuKα radiation. These peak positions may vary within a range of ±0.5° or ±0.3°, respectively.
[0014] The composition of the LiSi precursor is not particularly limited. The LiSi precursor may contain only Li and Si elements, or may contain other elements in addition to Li and Si elements. The total ratio of Li and Si elements to all elements contained in the LiSi precursor may be, for example, 50 mol% or more, 70 mol% or more, or 90 mol% or more. In the LiSi precursor, the ratio of Li to the total of Li and Si elements may be, for example, 30 mol% or more, 50 mol% or more, or 80 mol% or more, and may be 95 mol% or less, or 90 mol% or less.
[0015] The LiSi precursor may be obtained by mixing a raw material containing Li element and a raw material containing Si element. For example, in the manufacturing method of the present disclosure, a LiSi precursor may be obtained by mixing Si particles and Li metal. Examples of the mixing method include a method of mixing Si particles and Li metal using an agate mortar, a method of mixing Si particles and Li metal using a mechanical milling method, and the like. The temperature and pressure during mixing are not particularly limited. Heating or cooling may or may not be performed during mixing, and pressurization or decompression may or may not be performed. The atmosphere during mixing is also not particularly limited, and may be, for example, an inert gas atmosphere such as an Ar atmosphere. The shape and size of the Si particles and Li metal to be mixed are also not particularly limited, and may be appropriately selected according to the shape and size of the target active material.
[0016] 1.2 Extraction of Li element and formation of voids The voids are formed by extracting the Li element from the LiSi precursor. A Li extraction solvent is used to extract the Li element. For example, the LiSi precursor is brought into contact with the Li extraction solvent, whereby the Li extraction solvent reacts with Li, and the Li element is extracted from the LiSi precursor to the Li extraction solvent. The form in which the LiSi precursor is brought into contact with the Li extraction solvent is not particularly limited, and the LiSi precursor may be immersed in the Li extraction solvent, the Li extraction solvent may be sprayed onto the LiSi precursor, the LiSi precursor may be mixed with the Li extraction solvent, or the LiSi precursor may be dispersed in a dispersion medium to form a dispersion liquid, and the dispersion liquid may be mixed with the Li extraction solvent.
[0017] In particular, when the manufacturing method of the present disclosure includes dispersing the LiSi precursor in a dispersion medium to obtain a dispersion liquid, and mixing the dispersion liquid with a Li extraction solvent to extract Li element from the LiSi precursor to form voids, the pore size of the active material after Li extraction is more easily adjusted appropriately. Examples of the dispersion medium include one or more solvents selected from saturated hydrocarbons such as n-heptane, n-octane, n-decane, 2-ethylhexane, and cyclohexane, unsaturated hydrocarbons such as hexene and heptene, aromatic hydrocarbons such as 1,3,5-trimethylbenzene, toluene, xylene, ethylbenzene, propylbenzene, cumene, 1,2,4-trimethylbenzene, and 1,2,3-trimethylbenzene, and ethers such as n-butyl ether, n-hexyl ether, isoamyl ether, diphenyl ether, methyl phenyl ether, and cyclopentyl methyl ether. Among these, one or more selected from n-butyl ether, 1,3,5-trimethylbenzene and n-heptane are preferred, and 1,3,5-trimethylbenzene is particularly preferred. The water content in the dispersion medium is preferably low. This is because water reacts with the LiSi precursor. The water content in the dispersion medium may be, for example, 100 ppm or less, 50 ppm or less, 30 ppm or less, or 10 ppm or less. The ratio (solid content ratio) of the LiSi precursor in the dispersion liquid is not particularly limited, and may be a ratio that allows the LiSi precursor to be dispersed in the dispersion medium. The dispersion liquid is obtained, for example, by mixing the LiSi precursor with the dispersion medium. In this case, the mixing means is not particularly limited.
[0018] The temperature and pressure when extracting Li element from LiSi precursor using Li extraction solvent are not particularly limited. Heating or cooling may or may not be performed during Li extraction, and pressurization or decompression may or may not be performed. The atmosphere during Li extraction and the Li extraction time are also not particularly limited. In addition, the ratio of LiSi precursor to Li extraction solvent during Li extraction is also not particularly limited. The temperature, pressure, time, ratio, etc. may be adjusted so that the required amount of Li can be extracted from the LiSi precursor.
[0019] In the manufacturing method of the present disclosure, voids are formed by extracting Li element from a LiSi precursor using a Li extraction solvent. The voids formed in the active material after Li extraction have various pore diameters. Here, by adjusting the pore diameter in the active material after Li extraction, the pores become less likely to collapse even when the active material is pressurized (for example, when an electrode is pressed during battery production). According to the findings of the present inventors, by increasing the amount of pores with a diameter of 55 nm or less in the active material, the pores become less likely to collapse, and the expansion and contraction of the active material during charging and discharging can be further suppressed.
[0020] On the other hand, according to the findings of the present inventor, when Li is extracted from a LiSi precursor, the Li extraction rate differs depending on the type of Li extraction solvent, and the diameter of the pores formed after Li extraction changes. It is considered that the greater the carbon number of the Li extraction solvent and the greater the steric hindrance, the more difficult it is to react with Li. Specifically, the Li extraction rate is fastest when methanol is used, followed by ethanol, then 1-propanol, and then isopropanol. In addition, the pore diameter after Li extraction is most likely to be large when methanol is used, followed by ethanol, then 1-propanol, and then isopropanol. More specifically, when only ethanol is used as the Li extraction solvent, pores having a diameter of less than 10 nm are unlikely to be formed in the active material after Li extraction. In addition, when only propanol is used as the Li extraction solvent, pores having a diameter of less than 10 nm are likely to be formed in the active material after Li extraction, but the ability to form pores having a diameter of 20 to 55 nm is smaller than that of ethanol. Furthermore, when only methanol is used as the Li extraction solvent, pores having a diameter exceeding 45 nm are easily formed in the active material after Li extraction. That is, when ethanol, methanol, or propanol are used as the Li extraction solvent in combination of two or more of them, the amount of pores having a diameter of 55 nm or less increases, and the collapse of the pores when pressurized is suppressed, and the expansion and contraction of the active material during charging and discharging is easily suppressed. According to the findings of the present inventors, when the Li extraction solvent contains ethanol and one or more of methanol and propanol, among them, when the Li extraction solvent contains ethanol and propanol, and further among them, when the Li extraction solvent contains ethanol, methanol, and 1-propanol, the amount of pores having a diameter of 55 nm or less in the active material after Li extraction is more likely to increase. The mass ratio of ethanol, methanol, and propanol in the Li extraction solvent is not particularly limited, and may be appropriately adjusted according to the target pore diameter and pore amount.
[0021] In this application, "propanol" refers to 1-propanol, isopropanol, or a combination thereof. In addition, in this application, "the Li extraction solvent contains two or more selected from the group consisting of ethanol, methanol, and propanol" means that the Li extraction solvent contains at least ethanol and methanol, at least ethanol and propanol, at least methanol and propanol, or at least ethanol, methanol, and propanol. In other words, the case where the Li extraction solvent contains 1-propanol and isopropanol and does not contain ethanol and methanol does not fall under the Li extraction solvent of the present disclosure.
[0022] The Li extraction solvent may contain two or more selected from the group consisting of ethanol, methanol, and propanol, and may further contain other auxiliary solvents. The auxiliary solvent may be any solvent that does not adversely affect the formation of voids. Examples of auxiliary solvents include the acids described below. In the manufacturing method of the present disclosure, the total of two or more selected from the group consisting of ethanol, methanol, and propanol may account for 50% by mass or more, 70% by mass or more, 90% by mass or more, 95% by mass or more, or 99% by mass or more of the Li extraction solvent.
[0023] The extraction of the Li element may be performed in one step, or in two or more steps. For example, an active material having voids may be obtained in one step by only reacting the LiSi precursor with the Li extraction solvent, or after the formation of voids using the Li extraction solvent, the Li element may be extracted again using the Li extraction solvent, or Li may be extracted using an acid, and the active material may be obtained through two or more extraction steps. By using an acid after using the Li extraction solvent, the Li element can be more appropriately extracted from the LiSi precursor. Examples of the acid include one or more of acetic acid, formic acid, propionic acid, and oxalic acid. Acetic acid is particularly preferred. The temperature, pressure, time, volume ratio, etc. during the Li extraction using an acid are not particularly limited.
[0024] In the manufacturing method of the present disclosure, the active material after Li extraction may be optionally washed. This can reduce impurities contained in the active material. If the concentration of the LiSi precursor in the total of the LiSi precursor and the Li extraction solvent is high, the manufacturing efficiency is high, but the amount of impurities generated is likely to be large. For example, when the concentration of the LiSi precursor is 3.3 g or more per 1 L of the Li extraction solvent, the active material after Li extraction can be washed to improve the manufacturing efficiency and reduce the impurities. The washing may be, for example, an acid washing in which the active material is brought into contact with an acid. The above-mentioned extraction of Li element by an acid may also serve as the acid washing of the active material.
[0025] The active material obtained as described above may be recovered by any method. For example, the active material can be recovered by separating the solid reactant (active material) from the dispersion after Li extraction or the dispersion after washing, and drying it.
[0026] 2.Active material The technology of the present disclosure also has an aspect as an active material itself. For example, the active material of the present disclosure is a porous active material containing Si, and contains 0.21 cc / g or more of pores having a diameter of 55 nm or less. By containing 0.21 cc or more of pores having a diameter of 55 nm or less per 1 g of active material, as described above, the collapse of the pores when pressurized is suppressed, and the expansion and contraction of the active material during charging and discharging is easily suppressed. The active material of the present disclosure may contain 0.22 cc / g or more, or 0.23 cc / g or more of pores having a diameter of 55 nm or less, or may contain 0.30 cc / g or less, 0.28 cc / g or less, or 0.26 cc / g or less. The amount of pores having a diameter of 55 nm or less contained in the active material can be determined, for example, from the pore size distribution by nitrogen gas adsorption method or DFT method.
[0027] The composition of the active material of the present disclosure is not particularly limited. The ratio of the Si element to all elements contained in the active material of the present disclosure may be, for example, 50 mol% or more, 70 mol% or more, or 90 mol% or more. The active material of the present disclosure may contain Li element in addition to the Si element. It may also contain impurities such as oxides. The active material of the present disclosure may be amorphous or crystalline. The crystal phase contained in the active material of the present disclosure is not particularly limited.
[0028] The active material of the present disclosure may be particulate. The average primary particle diameter of the active material of the present disclosure may be 50 nm or more, 100 nm or more, or 150 nm or more, and may be 3000 nm or less, 1500 nm or less, or 1000 nm or less. The average secondary particle diameter of the active material of the present disclosure may be 1 μm or more, 2 μm or more, 5 μm or more, or 7 μm or more, and may be 60 μm or less, or 40 μm or less. The average primary particle diameter and the average secondary particle diameter can be determined, for example, by observation with a SEM, and are determined, for example, as the average value of the maximum Feret diameters of a plurality of particles. The number of samples is preferably large, and is, for example, 20 or more, 50 or more, or may be 100 or more. The average primary particle diameter and the average secondary particle diameter can be appropriately adjusted, for example, by appropriately changing the manufacturing conditions of the active material or performing a classification process.
[0029] The active material of the present disclosure may have a predetermined porosity. The porosity may be 5% or more, 10% or more, or 20% or more, and may be 50% or less, 40% or less, or 30% or less. The porosity can be determined, for example, by observation using a scanning electron microscope (SEM). It is preferable to have a large number of samples, for example, 100 or more. The porosity can be an average value determined from these samples.
[0030] The active material of the present disclosure may be either a positive electrode active material or a negative electrode active material. In particular, it is preferably a negative electrode active material. In addition, the use of the active material of the present disclosure is not particularly limited, but it is preferably used in, for example, a lithium ion secondary battery. In particular, it is preferably used in a lithium ion secondary battery containing a solid electrolyte, particularly an inorganic solid electrolyte, particularly a sulfide solid electrolyte. This is because the change in the confining pressure due to the expansion and contraction of the active material is likely to be large in a lithium ion secondary battery containing a solid electrolyte, and by using the active material of the present disclosure, the change in the confining pressure can be reduced.
[0031] 3. Lithium-ion secondary battery manufacturing method and lithium-ion secondary battery The technology of the present disclosure also has an aspect as a manufacturing method of a lithium ion secondary battery and an aspect as a lithium ion secondary battery. That is, the manufacturing method of a lithium ion secondary battery of the present disclosure includes manufacturing an active material by the manufacturing method of the present disclosure, obtaining a positive electrode, obtaining a negative electrode, and forming an electrolyte layer between the positive electrode and the negative electrode, and is characterized in that the active material is used as either a positive electrode active material in the positive electrode or a negative electrode active material in the negative electrode. Also, the lithium ion secondary battery of the present disclosure includes a positive electrode, a negative electrode, and an electrolyte layer, and one of the positive electrode and the negative electrode contains the active material of the present disclosure.
[0032] As described above, the active material of the present disclosure is preferably used as a negative electrode active material. The configuration of the positive electrode and the negative electrode other than the active material is the same as that of the conventional one, so detailed description will be omitted. In addition, the electrolyte layer preferably contains a solid electrolyte, particularly an inorganic solid electrolyte, among others, a sulfide solid electrolyte. Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5-GeS2, and the like. In particular, the performance of a sulfide solid electrolyte containing at least Li, S, and P as constituent elements is high.
[0033] In the lithium ion secondary battery of the present disclosure, the active material of the present disclosure is used as the positive electrode active material or the negative electrode active material, so that the expansion and contraction of the active material during charging and discharging can be suppressed, and the restraining pressure of the battery is unlikely to increase excessively. As a result, for example, the input / output characteristics and cycle characteristics of the battery can be easily improved.
[0034] The positive electrode, negative electrode, and electrolyte layer of the lithium ion secondary battery of the present disclosure can be produced, for example, as follows. However, the method is not limited to the following method, and each layer may be formed, for example, by dry molding. (1) A negative electrode active material and the like are dispersed in a solvent to obtain a negative electrode slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. Thereafter, the negative electrode slurry is applied to the surface of a negative electrode current collector or an electrolyte layer described later using a doctor blade or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode current collector or the electrolyte layer, thereby forming a negative electrode. Here, the negative electrode active material layer may be press-molded. (2) The positive electrode active material and the like are dispersed in a solvent to obtain a positive electrode slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. Thereafter, the positive electrode slurry is applied to the surface of a positive electrode current collector or an electrolyte layer described later using a doctor blade or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode current collector or the electrolyte layer, thereby forming a positive electrode. Here, the positive electrode active material layer may be press-molded. (3) The layers are laminated so as to sandwich the electrolyte layer between the negative electrode and the positive electrode to obtain a laminate having a negative electrode current collector, a negative electrode active material layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode current collector in this order. The electrolyte layer may be obtained by, for example, molding an electrolyte mixture containing an electrolyte and a binder, or may be obtained by press molding. Alternatively, when manufacturing an electrolyte battery, a separator that becomes the electrolyte layer may be sandwiched between the negative electrode active material layer and the positive electrode active material layer. Here, the laminate may be further press molded. Other members such as terminals are attached to the laminate as necessary. (4) The laminate is housed in a battery case and sealed to obtain a lithium ion secondary battery. When an electrolyte battery is produced, the laminate may be housed in a battery case together with an electrolyte and sealed. EXAMPLES
[0035] The technology of the present disclosure will be described in more detail below with reference to examples, but the technology of the present disclosure is not limited to the following examples.
[0036] 1. Preparation of active material for evaluation 1.1 reference Example 1 1.1.1 Preparation of LiSi precursor 0.65 g of Si particles (particle size 0.5 μm, manufactured by Kojundo Chemical Co., Ltd.) and 0.60 g of Li metal (manufactured by Honjo Metal Co., Ltd.) were mixed in an agate mortar in an Ar atmosphere to obtain a LiSi precursor.
[0037] 1.1.2 Preparation of LiSi precursor dispersion In a glass reactor under an Ar atmosphere, 1.0 g of the LiSi precursor and 125 ml of a dispersion medium (1,3,5-trimethylbenzene, manufactured by Nacalai Tesque) were mixed using an ultrasonic homogenizer (UH-50, manufactured by SMT Corporation) to obtain a dispersion liquid.
[0038] 1.1.3 Extraction of Li element using Li extraction solvent Ethanol (manufactured by Nacalai Tesque), methanol (manufactured by Nacalai Tesque), and isopropanol (manufactured by Nacalai Tesque) were mixed in a mass ratio of 85.5:13.4:1.1 to obtain a Li extraction solvent. The above dispersion was cooled to 0°C, and 125 ml of the above Li extraction solvent was added dropwise thereto and reacted for 120 minutes.
[0039] 1.1.4 Extraction of Li element with acid After the reaction with the Li extraction solvent, 50 ml of acetic acid (Nacalai Tesque) was added dropwise and the reaction was allowed to proceed for 60 minutes.
[0040] 1.1.5 Recovery of active material After the reaction, the liquid and the solid reactant were separated by suction filtration. The obtained solid reactant was vacuum dried at 120° C. for 2 hours and collected as an active material for evaluation.
[0041] 1.2 Example 2 The Li extraction solvent used was a mixture of ethanol, isopropanol, and 1-propanol (manufactured by Nacalai Tesque) in a mass ratio of 85.5:4.9:9.6. reference An active material was prepared in the same manner as in Example 1.
[0042] 1.3 Example 3 The Li extraction solvent used was a mixture of ethanol, methanol, and 1-propanol in a mass ratio of 85.5:4.9:9.6. reference An active material was prepared in the same manner as in Example 1.
[0043] 1.4 Comparative Example 1 Except for using ethanol alone as the Li extraction solvent, reference An active material was prepared in the same manner as in Example 1.
[0044] 1.5 Comparative Example 2 Except for using 1-propanol alone as the Li extraction solvent, reference An active material was prepared in the same manner as in Example 1.
[0045] 2. Measurement of pore size and volume The amount of pores with diameters of 55 nm or less contained in the active material was determined from the pore size distribution measured by nitrogen gas adsorption and DFT methods.
[0046] 3. Preparation of Evaluation Battery 3.1 Synthesis of sulfide solid electrolyte 0.550g of Li2S (Furuuchi Chemical), 0.887g of P2S5 (Aldrich), 0.285g of LiI (Nippo Chemical), and 0.277g of LiBr (Kojundo Chemical) were mixed in an agate mortar for 5 minutes. 4g of n-heptane (dehydrated grade, Kanto Chemical) was added to the mixture and mechanically milled for 40 hours using a planetary ball mill to obtain a sulfide solid electrolyte.
[0047] 3.2 Preparation of positive electrode mixture LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A positive electrode active material was obtained by surface-treating LiNbO3 on LiNbO2 (manufactured by Nichia Corporation). 1.5 g of this positive electrode active material, 0.023 g of conductive additive (VGCF, manufactured by Showa Denko), 0.239 g of the above solid electrolyte, 0.011 g of binder (PVdF, manufactured by Kureha), and 0.8 g of butyl butyrate (manufactured by Kishida Chemical Industry Co., Ltd.) were mixed using an ultrasonic homogenizer (UH-50, manufactured by SMT Corporation) to obtain a positive electrode composite material.
[0048] 3.3 Preparation of negative electrode mixture reference Example 1~ 2. Example 3. 1.0 g of the active material of either Comparative Example 1 or 2, 0.04 g of a conductive additive (VGCF, manufactured by Showa Denko), 0.776 g of the above solid electrolyte, 0.02 g of a binder (PVdF, manufactured by Kureha), and 1.7 g of butyl butyrate (manufactured by Kishida Chemical) were mixed using an ultrasonic homogenizer (UH-50, manufactured by SMT Corporation) to obtain a negative electrode composite.
[0049] 3.4 Battery Construction 1cm 2 0.065 g of the above solid electrolyte was placed in a ceramic mold at 1 ton / cm 2 The separator layer (solid electrolyte layer) was prepared by pressing the separator with a pressure of 1 ton / cm. 2 The positive electrode active material layer was prepared by pressing the negative electrode mixture (0.0054 g) at a pressure of 4 ton / cm. 2An aluminum foil serving as a positive electrode current collector was laminated on the positive electrode active material layer, and a copper foil serving as a negative electrode current collector was laminated on the negative electrode active material layer to prepare a battery for evaluation.
[0050] 4. Measurement of the increase in confining pressure The evaluation battery was CC / CV charged at 0.245 mA to 4.55 V, and then CC / CV discharged at 0.245 mA to 3.0 V. In the first charge, the confining pressure of the battery was monitored, and the confining pressure at 4.55 V was measured. The confining pressure in the battery using the active material of Comparative Example 1 was set to 1.00, and the confining pressure in Comparative Example 2 and Comparative Example 3 was set to 1.00. reference Example 1~ 2. Example The confinement pressure in the batteries using the three active materials was evaluated comparatively.
[0051] 5. Evaluation Results In Table 1 below, reference Example 1~ 2. Example For each of Comparative Examples 1 and 2 and No. 3, the type of Li extraction solvent used in the production of the active material, the amount of pores with a diameter of 55 nm or less contained in the active material, and the increase in the confining pressure of the evaluation battery are shown.
[0052] [Table 1]
[0053] From the results shown in Table 1, it can be seen that when a mixed solvent of two or more selected from ethanol, methanol, and propanol is used as the Li extraction solvent, the amount of pores with a diameter of 55 nm or less in the active material after Li extraction is increased compared to when ethanol or propanol is used alone. This is thought to be due to the fact that the reaction rate with Li differs depending on the type of solvent, and the size of the pores formed also changes. Specifically, the greater the carbon number of the Li extraction solvent and the greater the steric hindrance, the more difficult it tends to react with Li. As far as the inventors have confirmed, the Li extraction rate is fastest when methanol is used, followed by ethanol, then 1-propanol, and then isopropanol. In addition, the pore diameter after Li extraction is likely to be largest when methanol is used, followed by ethanol, then 1-propanol, and then isopropanol.
[0054] Figure 2 shows a plot of the relationship between the amount of pores with a diameter of 55 nm or less and the increase in the confining pressure, based on the results shown in Table 1 above. As is clear from Figure 2, the increase in the amount of pores with a diameter of 55 nm or less contained in the active material significantly reduces the increase in the confining pressure during charging. Pores with a diameter of 55 nm or less are unlikely to be crushed even when pressed during battery production, and exist appropriately as pores, which is thought to be effective in absorbing the expansion of the active material.
[0055] In Figure 3 reference Example 1~ 2. Example The relationship between pore size and pore volume is shown for each of the active materials of Comparative Examples 1 and 2 and Comparative Examples 3 and 3. The results shown in FIG. 3 reveal the following. First, when only ethanol is used as the Li extraction solvent (Comparative Example 1), pores having a diameter of less than 10 nm are unlikely to be formed in the active material after Li extraction. Also, when only propanol is used as the Li extraction solvent (Comparative Example 2), pores having a diameter of less than 10 nm are formed in the active material after Li extraction, but the ability to form pores having a diameter of 20 to 55 nm is smaller than that of ethanol. Also, when the amount of methanol in the Li extraction solvent is large ( referenceIn Example 1, pores having a diameter exceeding 45 nm are easily formed in the active material after Li extraction. When the Li extraction solvent contains two or more selected from the group consisting of ethanol, methanol, and propanol ( reference Example 1~ 2. Example 3) It can be seen that many pores with diameters of 55 nm or less are formed in the active material after Li extraction.
[0056] 6. Supplementary Information In the above embodiment, the LiSi precursor is dispersed in a dispersion medium to obtain a dispersion liquid, and then the dispersion liquid is mixed with a Li extraction solvent to extract the Li element, but the technology of the present disclosure is not limited to this embodiment. It is considered that the Li element can be extracted by contacting the LiSi precursor with the Li extraction solvent, and various methods can be adopted as the contact method.
[0057] In the above examples, the active material after the Li element is extracted with the Li extraction solvent is further treated with acetic acid, but the technology of the present disclosure is not limited to this form. From the results shown in Figure 3, it is clear that the pore size and pore volume of the active material are adjusted by the type of Li extraction solvent, and the subsequent acid treatment is optional.
[0058] In the above examples, the active material after Li extraction is used as the negative electrode active material, but the active material can also be used as the positive electrode active material. Furthermore, in the above examples, the case where an all-solid-state battery containing no liquid is produced as the evaluation battery is exemplified, but the technology of the present disclosure can also be applied to batteries other than all-solid-state batteries. However, the effect of the technology of the present disclosure is likely to be more pronounced when the active material after Li extraction is used as the negative electrode active material, and is likely to be more pronounced when the active material is applied to a lithium-ion secondary battery containing a solid electrolyte.
Claims
1. A method for producing an active material, comprising the steps of: Providing a LiSi precursor containing Li and Si elements; Extracting the Li element from the LiSi precursor using a Li extraction solvent to form voids; The Li extraction solvent includes ethanol, methanol, and 1-propanol; Manufacturing method.
2. Mixing Si particles and Li metal to obtain the LiSi precursor; Dispersing the LiSi precursor in a dispersion medium to obtain a dispersion; and Mixing the dispersion liquid with the Li extraction solvent to extract the Li element from the LiSi precursor to form voids. The method of claim 1 .
Citation Information
Patent Citations
Layered material, porous structure and producing method thereof
JP2019210194A
Negative electrode active material, manufacturing method thereof, and battery
JP2021022554A
Manufacturing method of active material
JP2021166153A
Active material, all-solid-state battery and manufacturing method of active material
JP2022077326A